Clinical Efficacy of Cycloferon in Complex Therapy of Infectious Mononucleosis in Pediatrics - E. B. Kasymova; O. A. Bashkina; KH. M. Galimzyanov (Антибиотики и Химиотерапия)
The results of the cycloferon use in therapy of 80 children at the age of 1 to 15 years with infectious mononucleosis are presented. The children were divided by chance sampling into two comparable groups of 40 subjects each. In the first group the children in addition to the standard therapy were treated with cycloferon for 10 days, intramuscularly or orally depending on the age. The reference group included the patients under the standard therapy alone. The efficacy of the drug was evaluated by reduction and more rapid disappearance of the main clinical symptoms of the disease. The improvement of certain laboratory indices, including those of the liver protein synthesis function were recorded, that allowed to reduce the hospitalization term. No side effects of the cycloferon use were observed.